Detection of bovine parvovirus proteins homologous to the nonstructural NS-1 proteins of other autonomous parvoviruses. - Lederman, M (1987)
Two nonstructural proteins of bovine parvovirus (BPV) with apparent molecular sizes of 75,000 and 83,000 daltons have been detected. The proteins were immunoprecipitated from lung cells infected with various isolates of BPV and from in vitro translations of infected cell mRNA. These proteins were expressed as nuclear phosphoproteins and were synthesized early in infection, before the peak of capsid protein synthesis. Early in infection, the 75-kilodalton-size species could be resolved into two bands of equal intensity, but later in infection, the lower-molecular-size form predominated. Antibodies directed against bacterial fusion proteins encoding amino acid sequences from a highly conserved region of the NS-1 polypeptides of two other parvoviruses, minute virus of mice and the human virus B19, gave specific nuclear fluorescence with BPV-infected cells, although the antibodies failed to immunoprecipitate any viral proteins. The noncapsid proteins appear to be homologous to the previously characterized NS-1 proteins of other autonomous parvoviruses.